Challenges Security Aspects and Solutions for Migrating From IPv4 TO IPv6: Addressing the Challenges of Migrating from IPv4 to IPv6 (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Internet Protocol (IP) is the ubiquitous internetworking protocol that drives the internet and world business communication channel today. The protocol permits millions of users to communicate and share information over the World Wide Web. Originally conceived in 1974 by Vinton G Cerf and Robert E Kahn, Internet Protocol Version 4 (IPv4) which was developed almost three decades ago is the mostly pervasive protocol version in use today. However, with the expeditious and exponential growth of internet and increase in number of connected devices, we are facing a scenario where IPv4 addresses are potentially exhausted. The IPv4 extensions such as NAT, CIDR and Sub netting etc. are merely limited short-term solutions. Moreover the scalability and security features that are required by the modern Internet can’t be fulfilled by IPv4. The long term solution to these problems is a step-by-step, phased but complete migration to IPv6. While IPv4 address space can hold billions of addresses, IPv6, which is the next version of the protocol, has provided trillions of addresses which are potentially inexhaustible. Thus evolution of new version of protocol i.e. IPv6 seems to be a flawless replacement choice for IPv4. However migration to IPv6 cannot be overnight due to prodigious installed network infrastructure base of IPv4.There needs to be seamless integration and co-existence between the two protocols for quite some time till migration process completes.IPv6 transition is not a transparent process for the layers above IP.